Peranan Public Relation Pada PT. Grapari Telkomsel Branch Manado - Bolung, Chevny; Kaunang, Markus; Londa, Very Y (JURNAL ILMIAH SOCIETY, 2015)
One of the efforts to achieve the goals in an organization is the implementation of an efficient public relations and effective. The purpose in this paper is to analyze the role of Public Relations at PT. Telkomsel Grapari Branch Manado. The methodology used is qualitative, data were collected through observation, interviews and literature studies. The number of informants 17 people. The data obtained were related to the role of public relations then analyzed through categorization and data reduction. The final conclusion is that the role of public relations in Grapari Telkomsel Branch Manado, in this case has not been running with good views of the function as a communicator and as a relationship. So that should make improvements human resources through training, as well as in the form of the existing service system in Grapari Telkomsel Branch Manado. Public relations role played by customer service seen from the function as a communicator as well as the relationship is not going well. Keywords: Public Relations, Communicators, Relationship